Taphonomy and depositional environment of a Lower Cretaceous monospecific dinosaur bone assemblage (Puesto Quiroga Member, Lohan Cura Formation), Neuquén Province, Argentina - Garrido, Alberto Carlos (2015)
The Puesto Díaz Quarry (Lohan Cura Formation, Lower Cretaceous of Neuquén Basin, Argentina) consists of a monospecific dinosaur bone assemblage that includes 126 specimens from, at least, three individuals of the rebbachisaurid sauropod Comahuesaurus windhauseni. The bonebed was originated as a debris flow of an ephemeral-river bed, in distal areas of low relief. Bones are disarticulated, three-dimensionally distributed through the host facies, showing a normal grading arrangement, which can be correlated with the size, shape and hydraulic behavior inferred for each specimen. Taphonomic evidence suggests that the bones did not experience a prolonged transport, and that these were quickly buried by the debris flow event. The fact that there are more than one individual of the same species suggests a mass mortality by a catastrophic event. Scattered skeletal elements would indicate that the corpses must have been subaerially exposed, long enough to allow disarticulation by scavenging, decay, and defleshing.